The influence of phthalocyanine aggregation in complexes with CdSe/ZnS quantum dots on the photophysical properties of the complexes - Martynenko, Irina V.; Orlova, Anna O.; Maslov, Vladimir G.; Fedorov, Anatoly V.; Berwick, Kevin; Baranov, Alexander V. (Beilstein Journal of Nanotechnology, 2016)
The formation of nonluminescent aggregates of aluminium sulfonated phthalocyanine in complexes with CdSe/ZnS quantum dots causes a decrease of the intracomplex energy transfer efficiency with increasing phthalocyanine concentration. This was confirmed by steady-state absorption and photoluminescent spectroscopy. A corresponding physical model was developed that describes well the experimental data. The results can be used at designing of QD/molecule systems with the desired spatial arrangement for photodynamic therapy.
Keywords: aggregation; Förster resonance energy transfer; photosensitizer; semiconductor nanocrystals; tetrapyrroles